Viaje, memoria e identidad: problemáticas de la otredad en Viajes de la Amazonia a Malvinas de Beatriz Sarlo - Cerda, Susana (Verbum – Analecta Neolatina, 2021)
This paper examines how the discurse about otherness works in travel writing. It focuses attention on the work by Beatriz Salro, Viajes de la Amazonia a las Malvinas. The goal is to show how Sarlo negotiates and represents her identity, trips and memories as a traveller and travel writer. In this article the discussion that Sarlo establishes in her work it is framed within the tourist vs. traveler debate.